Physiotherapy Student Experiences of Developing Therapeutic Relationships whilst volunteering with the action after Stroke Charity - Aisling Byrne; Andrew Soundy; Carolyn Roskell (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2014)
Objectives: To explore physiotherapy students' experiences of patient-student relationship development, gained through volunteering with the Action after Stroke charity, with reference to usual placement experience, and to identify any changes in students' thoughts and feelings towards patients, and subsequent effect on relationship development. Design: An exploratory qualitative study, utilising field diaries and a focus group interview. Participants: Nine students who had volunteered with the charity for 11 weeks participated in the focus group.  Intervention: Students began recording their experiences in a field diary after 3 consecutive treatment sessions with a stroke patient and then participated in a focus group interview once volunteering had ended. Field diaries informed development of the focus group topic guides. Focus groups were audio recorded and transcribed verbatim. Thematic analysis of transcripts was undertaken. Findings: The following themes emerged from the data analysis: Time and continuity; Clinical education; Environmental factors; Trust, and Empathy. Students reported experiencing a qualitatively different and more satisfying therapeutic relationship with patients whilst working in the charity. They believed that patients benefitted from this enhanced therapeutic relationship. The time and space enabled trust and empathy to develop which helped them develop insight into their patients as people.  Conclusions: Participation in the Action after Stroke charity gave students a greater opportunity to develop positive therapeutic relationships compared to traditional placements, by increasing their confidence, independence, empathy, patient-centeredness and knowledge of patients' situations. Levels of trust also increased within the student-patient relationships. These findings suggest that involvement in non-standard practice placements, such as the charity, within a physiotherapy degree programme, may prove useful to students' professional development.